The Mango: Botany, Production and Uses 2009
DOI: 10.1079/9781845934897.0529
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest technology and quarantine treatments.

Abstract: This chapter reviews the technology and quarantine treatments that have been developed for the postharvest handling of mangoes. The following aspects are covered: considerations influencing postharvest requirements (market and consumer research, quality assurance and good agricultural practice); preharvest management (maturity, adjusting maturation time, skin colour and lenticel damage, storage life and physiological disorders, pests and diseases, weather conditions, and flavour and aroma); harvesting and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 0 publications
0
50
0
2
Order By: Relevance
“…Mango imports to the United States (US) and Europe have grown steadily in response to increased demand and affordable prices (Sauco 2004). When consumed regularly, mango can be a valuable dietary source of many phytochemical, which also impart a characteristic capusine yellow or reddish colour and distinct sweet rich flavour to the fruit which is contributed by the volatile flavour compounds present in it (Johnson et al 1997, Grundhofer et al 2001Haard and Chism 1996). It is also considered as a source of antioxidants including ascorbic acid (mango fruit provides about 50% of the recommended daily intake of vitamin C) and carotenoids, which are lipophilic radical scavengers found in many fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…Mango imports to the United States (US) and Europe have grown steadily in response to increased demand and affordable prices (Sauco 2004). When consumed regularly, mango can be a valuable dietary source of many phytochemical, which also impart a characteristic capusine yellow or reddish colour and distinct sweet rich flavour to the fruit which is contributed by the volatile flavour compounds present in it (Johnson et al 1997, Grundhofer et al 2001Haard and Chism 1996). It is also considered as a source of antioxidants including ascorbic acid (mango fruit provides about 50% of the recommended daily intake of vitamin C) and carotenoids, which are lipophilic radical scavengers found in many fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…For high-end markets, quality requirements are stringent and, apart from a desired light yellow color and the absence of defects, uniform shape and an adequate fruit size determine the marketability of the fruit (Johnson et al, 1997;Fukuda et al, 2013;Schulze et al, 2013). During post-harvest handling, quality control takes place, which, besides the elimination of defective fruits, includes the sorting according to size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Little information is available about dendritic spot disease of mango (Johnson & Hofman 2008), however it has been suggested that, the fungi which are responsible for anthracnose and stem end rot in mango are also involved in the occurrence of dendritic spot. As a range of fungi have been isolated from fruit infected with dendritic spot symptoms, no information is available to determine which fungus dominates in a particular mango growing area.…”
Section: Discussionmentioning
confidence: 99%